2011
DOI: 10.1159/000325168
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Personality Disorder Functioning Styles in Paranoid Schizophrenia

Abstract: Objectives: Personality disorder functioning styles might contribute to the inconclusive findings about alexithymic features in schizophrenia. We therefore studied the relationship between alexithymia and personality styles in paranoid schizophrenia. Methods: We administered the Chinese versions of the Toronto Alexithymia Scale (TAS-20), the Parker Personality Measure (PERM), the Positive and Negative Syndrome Scale as well as the Hamilton Anxiety and Depression Scales to 60 paranoid schizophrenia patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 124 publications
4
9
1
Order By: Relevance
“…Emotion awareness studies with relatively higher proportions (28%) did not report differences in emotion awareness (Henry et al, 2010). In contrast, studies that reported significant differences had far lower schizoaffective disorder rates (7% in our sample; 2% in van't Wout et al, 2010; and 0% in Yu et al, 2011). Likewise, in the emotion regulation studies, samples with higher proportion of schizoaffective disorder (22% in Henry et al, 2008; 39% in Perry et al, 2011; and 16% in Badcock et al, 2011 - personal communication from Drs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Emotion awareness studies with relatively higher proportions (28%) did not report differences in emotion awareness (Henry et al, 2010). In contrast, studies that reported significant differences had far lower schizoaffective disorder rates (7% in our sample; 2% in van't Wout et al, 2010; and 0% in Yu et al, 2011). Likewise, in the emotion regulation studies, samples with higher proportion of schizoaffective disorder (22% in Henry et al, 2008; 39% in Perry et al, 2011; and 16% in Badcock et al, 2011 - personal communication from Drs.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings regarding decreased emotion awareness in individuals with schizophrenia are consistent with previous reports (Stanghellini and Ricca, 1995; Cedro et al, 2001; van't Wout et al, 2010; Yu et al, 2011). An exception to this trend is the finding by Henry and colleagues who reported no differences between patients and healthy controls (Henry et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In schizophrenia research, lack of emotional awareness is often subsumed under the concept of alexithymia, a term referring to problems with identifying, describing, and communicating emotions, differentiating emotions from bodily experience, and experiencing emotional fantasy (Sifneos, 1973; Sifneos et al, 1977). A number of studies have shown people with schizophrenia demonstrate alexithymia or deficits in the area of emotional awareness (Cedro et al, 2001; Kubota et al, 2011; Lincoln et al, 2014; Van't Wout et al, 2007; Yu et al, 2011). These deficits have been linked to objective outcomes, such as poorer social support and relationship quality (Kimhy et al, 2012), reduced independent living (Tabak et al, 2015), and increased symptoms including depressed mood and delusions (D'Antonio et al, 2015).…”
mentioning
confidence: 99%
“…Only recently, there is a trend to increased research efforts regarding personality disorders (PDs) and maladaptive personality traits (MPTs) in patients with schizophrenia spectrum disorders (SSDs), with evidence for a clinically relevant level of comorbid PDs in SSDs (Huber, 2006;Newton-Howes et al, 2008;Schroeder et al, 2012). Furthermore, schizoid, schizotypal, and sociopathic traits have been discussed as risk factors of psychosis (Cuesta et al, 1999), have been found to predict transition to psychosis (Mason et al, 2004), shape expression of symptoms (Cuesta et al, 2002), show associations with cognitive dysfunctions (Cuesta et al, 2001), and predict alexithymia (Yu et al, 2011) as well as insight of illness (Campos et al, 2010;Cuesta et al, 2011). These findings are not limited to personality traits that have traditionally been connected with SSDs; avoidant PD, for example, was significantly associated with SSDs (Fogelson et al, 2007;Gooding et al, 2007), and comorbid borderline PD has been shown to have a significant negative longitudinal impact on the course and outcome of schizophrenia (Bahorik and Eack, 2010).…”
mentioning
confidence: 99%